Ion exchange behaviour of 42 selected elements on AG MP-50 cation exchange resin in nitric acid and citric acid mixtures - Van der Meulen, Nicholas (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2003.